Dose- and LET-dependent changes in mouse skin contracture up to a year after either single dose or fractionated doses of carbon ion or gamma rays. (10th January 2022) - Ando, Koichi; Yoshida, Yukari; Hirayama, Ryoichi; Koike, Sachiko; Matsufuji, Naruhiro
Abstract: Time dependence of relative biological effectiveness (RBE) of carbon ions for skin damage was investigated to answer the question of whether the flat distribution of biological doses within a Spread-Out Bragg peak (SOBP) which is designed based on in vitro cell kill could also be flat for in vivo late responding tissue. Two spots of Indian ink intracutaneously injected into the legs of C3H mice were measured by calipers. An equieffective dose to produce 30% skin contraction was calculated from a dose–response curve and used to calculate the RBE of carbon ion beams. We discovered skin contraction progressed after irradiation and then reached a stable/slow progression phase. Equieffective doses decreased with time and the decrease was most prominent for gamma rays and least prominent for 100 keV/μm carbon ions. Survival parameter of alpha but not beta in the linear-quadratic model is closely related to the RBE of carbon ions. Biological doses within the SOBP increased with time but their distribution was still flat up to 1 year after irradiation. The outcomes of skin contraction studies suggest that (i) despite the higher RBE for skin contracture after carbon ions compared to gamma rays, gamma rays can result in a more severe late effect of skin contracture. This is due to the carbon effect saturating at a lower dose than gamma rays, and (ii) the biological dose distribution throughout the SOBP remains approximately the same even one year after exposure.